2017
DOI: 10.1186/s12903-017-0359-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on subgingival bacteria in healthy subjects and patients with chronic periodontitis

Abstract: BackgroundCigarette smoking is known to increase the risk of periodontal destruction and developing chronic periodontitis (CP). It is also reported to affect the subgingival bacterial profile among CP patients. However, studies on the effect of smoking on the bacterial profile among healthy subjects are still limited. Therefore, the aim of this study was to investigate the impact of smoking on the subgingival bacterial profile in both healthy adults and CP patients.MethodsSubgingival plaque samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
4
34
0
4
Order By: Relevance
“…Studies [1][2][3][4] have shown that tobacco-smoking is a prospect of periodontal and peri-implant diseases, such as periodontitis and periimplantitis, respectively. Furthermore, outcomes of oral surgical interventions are undermined in tobacco smoking users compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [1][2][3][4] have shown that tobacco-smoking is a prospect of periodontal and peri-implant diseases, such as periodontitis and periimplantitis, respectively. Furthermore, outcomes of oral surgical interventions are undermined in tobacco smoking users compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the environmental factors involved in periodontitis, oral epithelial injury caused by the overgrowth of commensal microorganisms (dysbiosis) is considered the initiator of periodontal destruction, while smoking modulates disease progression . Indeed, smoking is a major risk factor and has been shown to stimulate periodontal destruction and increase the risk of periodontitis in young adults . Based on epidemiological studies, smokers have more severe chronic periodontitis (CP) than non‐smokers and the relationship is dose‐dependent, both in terms of the number of cigarettes smoked per day and the number of years of smoking .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, smoking is a major risk factor and has been shown to stimulate periodontal destruction and increase the risk of periodontitis in young adults . Based on epidemiological studies, smokers have more severe chronic periodontitis (CP) than non‐smokers and the relationship is dose‐dependent, both in terms of the number of cigarettes smoked per day and the number of years of smoking . ‒ …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations